Towards quantitative ecology : Newton's principia revisited - Hari, Pertti; Back, Jaana; Heliovaara, Kari; Kerminen, Veli-Matti; Kulmala, Liisa; Makela, Annikki; Nikinmaa, Eero; Petaja, Tuukka; Kulmala, Markku (Finnish Environment Institute, 2016)
Peer reviewed